The Relevance of David B. Resnik's Ethical Principles in Academic Writing and Research for Students - Sonya Pasaribu; Sonya S.M. Silitonga; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study investigates the application of David B. Resnik's ethical principles—honesty, objectivity, integrity, carefulness, and openness—in academic writing and research among students. Utilizing a mixed-methods approach, surveys and student paper analyses were conducted to measure awareness, adherence, and challenges. The results indicate that 95% of students are aware of general ethical principles in academic writing, yet only 70% are familiar with Resnik’s specific framework, leaving 30% unaware of these detailed concepts. Regarding practice, 100% of respondents consistently cited sources correctly, but 66% admitted to paraphrasing without proper attribution, showing gaps between ethical knowledge and application. Challenges identified include maintaining honesty (51%), avoiding plagiarism (29%), ensuring openness (11%), and minimizing bias (9%), often influenced by external pressures and resource limitations. To address these issues, students suggested practical solutions such as workshops, seminars, and digital guides to enhance understanding and compliance with ethical standards. This study emphasizes the importance of ethics education, institutional policy enhancements, and accessible resources to strengthen the implementation of academic integrity, bridging the gap between awareness and consistent ethical practice.